Potenciais evocados auditivos de tronco encefálico por frequência específica em crianças com e sem perda auditiva - Ramos, Natália (2012)
ABR) contributes to the early diagnosis of hearing loss, once it allows a precise assessment of small children in different frequencies. Aim: To analyze air and bone-conduction tone-ABR, in order to estimate hearing thresholds of children from birth to three years of age with normal hearing and with sensorineural or mixed hearing losses. Method: Sample was divided in two groups: group I (GI) with normal hearing newborns submitted to air and bone-conduction tone-ABR at 500, 1000, 2000 and 4000 Hz; the latency and the presence of wave V were analyzed up to 20 dBnHL; group II (GII) comprised children with hearing loss submitted to the same of tone-ABR testing as GI, and also to air and bone-conduction behavioral audiometry. Both procedures were correlated in this group. Results: An increase of wave V latency was observed in GI as the intensity decreased, as well as higher latencies in lower frequencies either for air or bone stimuli. Concerning the air-conduction testing at 500 Hz, wave V was present up to 30 dBnHL, and at 1000 Hz, 91,66% of subjects presented it at 20 dBnHL; all subjects presented responses at 20 dBnHL for the other frequencies. Concerning bone-conduction testing, all subjects presented wave V at 20 dBnHL for all frequencies. GII results showed strong correlation for all frequencies tested air-conduction; however, the bone-conduction testing showed a strong correlation at 500, 1000 and 2000 Hz, and moderate correlation at 4000 Hz. Conclusion: The air and bone-conduction tone-ABR at 500, 1000, 2000 and 4000 Hz is useful in the audiological diagnosis of children in this age group, and there is a good correlation between its results and the behavioral audiometry The latency of wave V behaves inversely proportional to intensity; airconduction responses at 30 dBnHL for 500 Hz, and air and bone-conduction responses at 20 dBnHL for other frequencies may be considered within normal limits